Glucometers for Patients with Type 2 Diabetes Mellitus: Are they helpful? - Andrew Thomas; Mohan T. Shenoy; K.T. Shenoy; Nirmal George (University Library System, University of Pittsburgh, 2021)
Background: The effectiveness of self-monitoring of blood glucose (SMBG) in type 2 diabetes mellitus (T2DM) patients is debated in the literature. We aimed at elucidating the association and patterns of complications between SMBG use and plasma glucose values. Methods: This cross-sectional study comprised 303 participants from outpatient departments with T2DM for over 12 months. We analyzed sociodemographic and clinical variables including: anthropometry, SMBG use, disease duration, treatment modality, complications, plasma glucose level, and glycated hemoglobin level (%). Results: The mean duration of T2DM was 93 ± 76 months. Participants were grouped into SMBG users (n=115, 38%) and non-SMBG users (n=188, 62%). The mean fasting plasma glucose levels of SMBG and non-SMBG users were 140.7±42.7 (95% Confidence Interval [95%CI]: 132.72;148.67) mg/dl and 145.4±50 (95%CI: 138.12;152.67) mg/dl (p=0.03), respectively. The mean post-prandial plasma glucose levels of the SMBG and non-SMBG groups were 202 ± 63.42 (95%CI: 190.23;213.76) mg/dl and 209±84.54 (95%CI: 196.56;221.43) mg/dl (p=0.002), respectively. The mean difference in HbA1c among the groups were 8.14±1.69% (95%CI: 7.59;8.68) and 8.15±1.98% (95%CI: 7.27;9.02) (p=0.4), respectively. Hypoglycemia (n=50, 43.5%) was the most common complication. The prevalence of neuropathy (n=5, 4.3%, p=0.036) and cardiovascular disease (n=21, 18.3%, p=0.042) were significantly higher in the SMBG group. Conclusion: Although plasma glucose values were significantly lower in the SMBG group, its clinical significance remains questionable. Furthermore, many participants in both groups had shortfalls in awareness, monitoring, and glycemic control. SMBG use needs to be evaluated in a cohort of patients with T2DM with adequate health awareness.